Primary Salivary Gland Tumors- A two years study at Nobel Medical College - Nepal, Niraj; Choudhary, Prabesh Kumar; Das, Manish Kumar; Basnet, Meenakshi; Paudel, Sagar (Nepalese Medical Journal, 2019)
Introduction: Salivary gland tumors are a heterogeneous group of neoplasms that are relatively rare but represent a wide variety of both benign and malignant histopathologic subtypes. The aim of this study was to find out the histopathological distribution of primary salivary gland tumors and correlate fine needle aspiration cytology reports with histological findings. Materials and Methods: A total of 83 patients attending the otorhinolaryngology department with salivary gland tumors were enrolled in our study. The histopathological findings were reported and correlated with cytological findings. Results: The mean age of the patient with salivary tumors was 43.11 ± 13.02 years. Out of 83 cases, 3 (3.6%) patients were diagnosed as inflammatory lesions, 64 (77.1%) patients had benign salivary gland tumors and 16 (19.3%) of patients had malignant salivary glands tumors in histopathology. The sensitivity and specificity of FNAC in this series for detecting salivary gland malignancy were 68.8% and 98.5% respectively with an overall diagnostic accuracy of 92.8%. The most common salivary gland tumor was found to be pleomorphic adenoma (56.6%) and the most common malignant salivary gland tumor was found to be mucoepidermoid carcinoma (19.3%). The comparison of the incidence of salivary gland tumors in various age groups showed a statistically significant difference (p=0.009). Conclusions: Benign salivary tumors are more common than malignant tumors with the most common occurrence in parotid glands. Pleomorphic adenoma is the most common benign tumor whereas; mucoepidermoid carcinoma is the most common malignant tumor in patients visiting Nobel medical college.